Configuration and innovation related network topology - Ela Ozkan-Canbolat; Aydin Beraha (Journal of Innovation & Knowledge (JIK), 2016)
Network topologies attract much theoretical attention in recent studies. Researchers adopt network topology models and assert that specific type of network topology improves product and process innovation. This study attempts to explore how network topology relates to product and process innovation in configurational terms. While this paper exploits interrelatedness between network topology configurations, and product and process innovation, it refers the firms outside contingencies obviously. Focusing on product and process innovation, outside contingencies rather than inside ones also make this paper natural to examine and contribute towards configurational theory.
Keywords: M10; M15; M19; 650; Network topology; Configurational theory; Product innovation; Process innovation